2019
DOI: 10.1093/rpd/ncz136
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of Algorithms Used to Estimate Effective Dose During Interventional Radiology Procedures

Abstract: In IR procedures, in order to evaluate the effective dose, the importance of the double dosemeter has been recognised, one worn above and one under the apron. Over the last few decades several algorithms have been developed to combine the readings of the dosemeters, however currently there is no international consensus on which is the best one. In this work, eight irradiations, corresponding to typical interventional radiology procedures, were carried out in order to experimentally verify the accuracy of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Following the conclusions of Negri et al [17], in this study we assume as the best estimate of the effective dose, E ref , the mean value (see equation ( 3)) of the following three algorithms of double dosimetry: (10) under + 0.05H p (10) over [18],…”
Section: Assessment Of the Effective Dosementioning
confidence: 99%
See 1 more Smart Citation
“…Following the conclusions of Negri et al [17], in this study we assume as the best estimate of the effective dose, E ref , the mean value (see equation ( 3)) of the following three algorithms of double dosimetry: (10) under + 0.05H p (10) over [18],…”
Section: Assessment Of the Effective Dosementioning
confidence: 99%
“…From our analysis we cannot identify which double-dosimetry algorithm provides the best assessment of the effective dose, but previous works showed that there is no ideal algorithm. Depending on the exposure situation [4,17] and also on the personal dosemeter calibration and performance [22] one algorithm can be considered better than another. In summary, the use of two dosemeters does not significantly improve the assessment of the effective dose in fluoroscopically guided interventional procedures, in general, except in situations where it is possible to approach or exceed the effective dose limit (20 mSv per year).…”
Section: Double-dosimetry Approachmentioning
confidence: 99%